Establishment of sheep nasal mucosa explant model and its application in antiviral research - Zheng, Jian; Lin, Jian; Ma, Yichao; Yang, Chengjie; Zhong, Qiu; Li, Yuchen; Yang, Qian (Frontiers in Microbiology, 2023)
The nasal mucosa is the first barrier to pathogen invasion through the respiratory tract. Few studies have focused on nasal resistance to invasion by respiratory pathogens due to the lack of models related to the nasal mucosa. Hence, it is necessary to construct a nasal mucosal model to study host-pathogen interactions. We established a long-term in vitro sheep nasal mucosa explant model (NMEM), which exhibited typical epithelial cilia and epithelial proliferation ability within 11 days. Moreover, to evaluate whether the NMEM was suited for in vitro pathogenic study, we used pseudorabies virus (PRV) and showed that it successfully infected and produced severe lesions in the NMEM, particularly interferon (IFN)-stimulated gene product 15 (ISG15). IFN decreased significantly after the PRV infection. Similarly, we used this NMEM model to screen several antiviral substances, such as probiotics and drugs. A previous study showed that nasal commensal bacteria, particularly Bacillus subtilis, had high antiviral activity. Then, we used the NMEM to evaluate six sheep-derived B. subtilis strains and demonstrated that it significantly induced the production of IFN and expression of ISG15. The sheep-derived B. subtilis was pretreated with the sheep NMEM before the PRV infection to evaluate the antiviral effect. The results showed that NSV2 significantly inhibited infection by PRV and reduced the viral load (p < 0.05). Furthermore, NSV2 may inhibit PRV replication by enhancing ISGylation of cells. In conclusion, we established a reliable in vitro culture model of sheep NMEM, and applied it in antiviral research.